Background and evaluation design of a community-based health-promoting school intervention: Fit Lifestyle at School and at Home (FLASH) - Bonnie Maria van Dongen; Monica Antonia Maria Ridder; Ingrid Hendrika Margaretha Steenhuis; Carry Mira Renders (BMC, 2019)
Abstract Background A community-based approach can be a promising strategy for implementing school-based health promotion aimed at stimulating healthy physical activity and dietary behaviour. Such an approach builds on the community capacity of multiple stakeholders, empowering them to design and implement tailored activities, supported by the whole school community. This paper describes the background and evaluation design of the community-based school intervention 'Fit Lifestyle at School and at Home' (FLASH) in four prevocational schools. FLASH includes four strategies for building the community capacity of students, school personnel and parents: 1) identifying leaders in each stakeholder group, 2) stimulating a school culture of participation, 3) having stakeholders design and implement tailored activities and 4) creating a network of local partners for structural embedding. The objective is to monitor the capacity-building processes of the FLASH intervention and to explore if these processes contribute to changes in community capacity. In addition, we will explore if the FLASH intervention is related to changes in PA, dietary behaviours and BMI of students. Methods This study has a mixed methods design and uses a participatory action-oriented approach to monitor and evaluate changes in community capacity, tailored health-promotion activities and implementation processes. Methods include semi-structured interviews, focus groups, journals, document analysis and observational scans of the physical environment. In addition, changes in BMI, physical activity and dietary behaviours of prevocational students will be explored by comparing the four intervention schools to four control schools. Data are collected by questionnaires and anthropometric measurements. Discussion The main strength of this study is its use of mixed methods to evaluate real-life processes of creating a healthy-school community. This will provide valuable information on capacity-building strategies for the structural embedding of health-promotion activities within school settings. The results could help schools become more empowered to adapt and adopt integral health-promotion interventions in daily practice that suit the needs of their communities, that are expected to be sustainable and that could lead to favourable changes in the PA and dietary behaviour of students. Trial registration ISRCTN67201841; date registered: 09-05-2019, retrospectively registered.